The Readiness of Teacher's Digital Capabilities Toward the Fourth Industrial Revolution Era (Industrial Revolution 4.0) - Muhammad Soleh Hapudin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this research was to determine the readiness and ability of teachers to face information and communication technology-based learning in the Industrial Revolution Era 4.0. The research method in this article is qualitative. The type is literature research, and the data analysis is descriptive analysis. Data obtained from library research. The data collection technique used by this researcher is a literature study. Data analysis techniques in this study use qualitative analysis techniques in a deductive way. Technology is developing exponentially, changing the way humans move, communicate, communicate and interact. Especially now that there is an era of the Industrial Revolution 4.0 known as the era of disruption. Education is one aspect affected by RI 4.0. Learning 4.0 requires a technological approach as a tool in the learning process. Teachers need to interconnect with subjects to gain relevant learning experiences. Teachers have only mastered basic applications commonly used daily, but are reluctant to learn to use new applications that can facilitate their work. Teachers in the digital era must have a mindset. In connection with that, teachers are required to be good at using technology in learning. The use of technology in learning is a necessity.